PENGARUH JAMINAN SOSIAL DAN INSENTIF TERHADAP KINERJA KARYAWAN - Ade Tiara Yulinda; Vista Marsella (UM. Bengkulu, 2021)
This study aims to determine what factors can affect the low performance of employees either partially or simultaneously. There are several factors that will be discussed in this study, including Social Security (X1) and Incentives (X2). The object of this research is all employees of PT. Matahari Department Store Tbk Bengkulu, amounting to 120 people. The sampling method in this research is Probability Sampling. In this study, the authors used data collection methods by means of observation, interviews, and questionnaires. There are several data analysis techniques used in this study, including by using instrument test, classical assumption test, respondent response analysis, multiple linear regression analysis, determinant coefficient, and hypothesis testing. From the results of the tests that have been carried out, it can be concluded that the variables of Social Security and Incentives have partially or simultaneously affected the performance of the employees of PT. Matahari Department Store Tbk Bengkulu.Keywords: Social Security, Incentives and Employee Performance.